Gendered Framing in Political Campaign Coverage: A Content Analysis of Selected Nigerian Newspapers - Luka, Luka Joshua; Ugondo, Peter (Darul Yasin Al Sys, 2025)
This study examines the gendered framing of political campaigns in selected Nigerian newspapers, focusing on how media narratives portray male and female political candidates and the implications for public perception and gender equity in political participation. Using content analysis, 120 newspaper articles, 30 each from The Punch, The Guardian, Vanguard, and ThisDay were analyzed to identify patterns in representation. The findings reveal a persistent reliance on stereotypical framing that reinforces traditional gender norms, thereby constraining women’s political engagement. By highlighting the role of media in shaping political discourse, the study advances understanding of how journalistic practices can either perpetuate or challenge gender bias in Nigeria’s political arena.